TiS3 Nanoribbons: A Novel Material for Ultra-Sensitive Photodetection across Extreme Temperature Ranges - Mohammad Talib; Nishant Tripathi; Samrah Manzoor; Prachi Sharma; Vladimir Pavelyev; Valentyn S. Volkov; Aleksey V. Arsenin; Sergey M. Novikov; Prabhash Mishra (Sensors, 2023)
Photodetectors that can operate over a wide range of temperatures, from cryogenic to elevated temperatures, are crucial for a variety of modern scientific fields, including aerospace, high-energy science, and astro-particle science. In this study, we investigate the temperature-dependent photodetection properties of titanium trisulfide (TiS3)- in order to develop high-performance photodetectors that can operate across a wide range of temperatures (77 K–543 K). We fabricate a solid-state photodetector using the dielectrophoresis technique, which demonstrates a quick response (response/recovery time ~0.093 s) and high performance over a wide range of temperatures. Specifically, the photodetector exhibits a very high photocurrent (6.95 × 10−5 A), photoresponsivity (1.624 × 108 A/W), quantum efficiency (3.3 × 108 A/W·nm), and detectivity (4.328 × 1015 Jones) for a 617 nm wavelength of light with a very weak intensity (~1.0 × 10−5 W/cm2). The developed photodetector also shows a very high device ON/OFF ratio (~32). Prior to fabrication, the TiS3 nanoribbons were synthesized using the chemical vapor technique and characterized according to their morphology, structure, stability, and electronic and optoelectronic properties; this was performed using scanning electron microscopy (SEM), transmission electron microscopy (TEM), Raman spectroscopy, X-ray diffraction (XRD), thermogravimetric analysis (TGA), and a UV–Visible–NIR spectrophotometer. We anticipate that this novel solid-state photodetector will have broad applications in modern optoelectronic devices.